The development and application of an experimental model of programme evaluation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Education at Massey University - Phillips, Sidney Hugh (Massey University, 1979)
This study reports on an investigation of three separate but ultimately related research areas relevant to the field of educational administration. The areas investigated were: (1) The development and current state of the New Zealand agricultural training system. (2) Flock House, a farm training institute controlled by the New Zealand Ministry of Agriculture and Fisheries. (3) The development, application and analysis of an experimental model of programme evaluation. The focus of the study was an evaluation of two agricultural short course programmes held at Flock House during 1978. Utilizing an experimental model of programme evaluation the researcher applied a three stage programme evaluation, to the two short courses. stage One of the evaluation process -- "apprehending" -- involved using procedures aimed at obtaining pre-course information from course members. Stago Two -- "acquisition" -- involved obtaining information from the course members regarding their views on the nature of the Flock House courses. Stage Three -- "application" -- involved the synthesis and application of the evaluation results and findings. Throughout the evaluation process the researcher relied upon the following information-gathering techniques. (1) Observation (2) Interviews (3) Questionnaires and test results (4) Documentary and background information (Parlett and Hamilton, 1972). The study concludes with the proposal of a blueprint for further evaluation of Flock House, and its implications.
Keywords: New Zealand; Flock House Farm (Bulls); Agriculture; Study and teaching